Helicobacter pylori infection in children: relation with current household living conditions. (July 1996) - McCallion, W A; Murray, L J; Bailie, A G; Dalzell, A M; O'Reilly, D P; Bamford, K B
Abstract : BACKGROUND: Studies demonstrating that deprived household living conditions during childhood are risk factors for acquisition of Helicobacter pylori infection have been performed mainly in adults, who probably acquired the infection several decades ago. This study investigates whether deprived household living conditions remain important risk factors for infection in subjects (children) with recently acquired infection. AIMS: To examine the relation between current household living conditions and acquisition of H pylori infection in childhood. SUBJECTS/SETTING: Opportunistically recruited group of 367 children, aged 3 to 15 years, undergoing routine non-gastrointestinal day surgery. METHODS: Anti-H pylori IgG antibodies measured by a commercial enzyme linked immunosorbent assay validated for use in children. Postal questionnaire collecting sociodemographic data and data on household living conditions. RESULTS: Infection was associated with social class and overcrowding in the household. After adjustment for age, social class, and household density, a positive association remained between infection with H pylori and bed-sharing between children and parents on one or two nights per week, odds ratio for infection (95% CI), 2.29 (1.21, 4.32) or more frequently, odds ratio for infection (95% CI), 2.95 (1.35, 6.45). CONCLUSIONS: The continuing importance of household living conditions in the acquisition of H pylori infection is confirmed and household crowding and sharing a bed with a parent are identified as risk factors for infection.